Virtual Lab Integration in Undergraduate Courses: Insights from Course Design and Implementation - Maria Papaconstantinou; Dawn Kilkenny; Christopher Garside; William Ju; Hedieh Najafi; Laurie Harrison (The Canadian Network for Innovation in Education (CNIE), 2021)
The instructors of four biology-related courses at a Canadian university integrated Labster virtual labs in their courses as a pre-lab activity, lecture substitute, or to provide lab experience in courses with no on-site labs. The instructors used a backward design approach to align the labs with the learning objectives of their courses and to connect the labs with their course assessments. A study was conducted to examine students' perceptions of the usefulness of the virtual labs in terms of content knowledge and lab skills. At the end of each course, the instructors administered an anonymous survey in their classes. In total, 370 students participated. Across all four courses, survey results showed that at least 77% of the students found that virtual lab simulations helped them understand course concepts. At least 74% of the students navigated the virtual labs with no issues and 58% of the students found the simulations to be of high quality.